Georgia Architectural and Historic Properties Survey of Barney [11] Unknown, Cecil, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Barney [11] Unknown, Cecil, Ga. December 1980. A one story Georgian plan with gabled roof and narrow clapboard siding. Hipped porch with turned spindle posts. Sash windows with 6/6 lights. Sidelights. Grape arbor. Good condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Town not extensive enough for a district.
Georgia Architectural and Historic Properties Survey of Barney [11] Unknown, Cecil, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 0.98 MB (1,037,116 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Barney, Ga.; Cecil, Ga.